Sonochemistry approach for a new process of biodiesel production from Jatropha Curcas Oil - Praptijanto, Achmad (2011)
This thesis presents the sonochemistry approach to reduce required reaction time to convert the Jatropha Curcas oil into biodiesel using an the ultrasound clamp on tubular reactor. The effect of diameter clamp on tubular reactor to remove free fatty acid (FFA) in the esterification process was investigated. The concentrations of methanol and catalyst in the transesterification process were clearly observed in this research. While in the purification process, the water concentration to oil, the output power and reaction time were investigated. The tube of diameter 60 mm removed FFA to below 1 % in 5 minutes. The optimum condition of the transesterification process was a molar ratio of methanol to oil of 7:1, catalyst concentration of 1 %, time of reaction of 5 minutes. Meanwhile the optimum condition of the purification process was at water concentration of 10 % (v/v), power output of 240 W, time of reaction of 5 minutes. The reaction time of esterification by clamp on tubular reactor reduces until 96 %, and transesterification reaction reduces until 83 % compared to conventional stirring method. The small pilot plant has been developed in this research according to the optimum condition. The average energy for one kg of biodiesel needed 0.06 kWh and 11 hour time of production process. In the performance engine and emission, this decreased of the brake specific fuel consumption (BSFC) and brake specific energy consumption (BSEC) could be due to lower heating value and higher density compared to diesel fuel. As an average amount of smoke density, was decreased to 60 % compared to diesel fuel. Average lessening of CO2 was determined as same as diesel fuel.